GLOBALIZED ECONOMY: OPPORTUNITIES AND CHALLENGES IN THE INTERNATIONALIZATION OF BUSINESS ORGANIZATIONS - Melo de Andrade Junior, Carlos (Revista Gênero e Interdisciplinaridade, 2023)
Globalization has promoted the interconnection of economies and cultures globally, boosting business internationalization as an essential strategy to access new markets and obtain competitive advantages. The search for success and sustainability in foreign markets requires adaptable and well-planned strategic approaches, allowing companies to establish their international presence in a solid and planned way. The search for international opportunities offers a promising horizon and managerial challenges for business growth. Addressing these challenges effectively enables companies to achieve sustainable success in a complex global environment. The internationalization of companies relates to ESG issues in the globalized environment, such as adapting to different environmental and social regulations and managing stakeholder expectations in different international markets. The approach method is inductive and the research technique is bibliographic. The main objective of this work is to analyze and highlight the relevance of business internationalization to expand its operations beyond national borders, seeking opportunities and mitigating challenges in international markets. To approach this topic, a concise explanation of themes that integrate the internationalization of companies is presented.